Mass vaccination response to a measles outbreak is not always possible. Lessons from a London prison. Issue 13 (19th July 2018) - Junghans, C.; Heffernan, C.; Valli, A.; Gibson, K.
Abstract: In this study, we describe a contained measles outbreak in a London prison, the second such outbreak in a custodial setting. Once vaccination commenced, just under a third of eligible prisoners were immunised due to a low uptake of the vaccine. We conducted a root-cause analysis in order to identify factors which may have prevented or altered the course of the outbreak. Our analysis revealed that many of the factors identified are those that cannot be easily changed. It is unlikely that mass vaccination at the time, even in the absence of some of the more easily rectifiable issues, could have fully avoided further cases in the event of a mass outbreak. Both measles outbreaks in a custodial setting started with a member of staff and immunisation status of the staff were largely unknown. We argue that mass vaccination following an outbreak in a prison is unlikely to fully prevent a mass outbreak, and that implementing opt-out testing, empirical vaccination and insisting on full immunisation of staff are most likely to both prevent and contain outbreaks in the future.